2017
DOI: 10.15210/sah.v5i1.9135
|View full text |Cite
|
Sign up to set email alerts
|

Fungos Predadores De Nematoides Em Amostras De Solo Do Município De Alegrete-Rs

Abstract: O controle das endoparasitoses representa um grande desafio em vista do desenvolvimento de resistência dos parasitas aos medicamentos anti-helmínticos disponíveis, o que estimula a busca por formas alternativas de controle. Os fungos nematófagos são espécies capazes de utilizar larvas de nematoides como forma de nutrição podendo ser classificados como ovicidas, endoparasitos ou predadores. Fungos predadores são telúricos, saprofíticos e, em condições especiais, produzem armadilhas tridimensionais para capturar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…The supply of isolates of predatory fungi is often not as simplified as it is related, acting time is varied, called the "grace period" because, at this time, specific conditions are needed for the activation and performance of nematophagous adequately (Carneiro, 1992). Studies have demonstrated the intervention of some variables in the maturation of fungi, which may become considerable problems over time (Vieira, 2017, Ferreira et al, 2016, Serra et al, 2017 Research, Society and Development, v. 12, n. 4, e21512441126, 2023 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v12i4.41126 9…”
Section: Predatory Fungi In Sheep Farmingmentioning
confidence: 99%
“…The supply of isolates of predatory fungi is often not as simplified as it is related, acting time is varied, called the "grace period" because, at this time, specific conditions are needed for the activation and performance of nematophagous adequately (Carneiro, 1992). Studies have demonstrated the intervention of some variables in the maturation of fungi, which may become considerable problems over time (Vieira, 2017, Ferreira et al, 2016, Serra et al, 2017 Research, Society and Development, v. 12, n. 4, e21512441126, 2023 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v12i4.41126 9…”
Section: Predatory Fungi In Sheep Farmingmentioning
confidence: 99%